2009
DOI: 10.1111/j.1472-8206.2009.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eslicarbazepine acetate on the pharmacokinetics of digoxin in healthy subjects

Abstract: Eslicarbazepine acetate (ESL) is a new-generation voltage-gated sodium channel blocker, which has been demonstrated to be effective and well tolerated in the treatment of epilepsy. The primary objective of this study was to investigate the effect of ESL on the pharmacokinetics of digoxin. This study was a randomized, double-blind, placebo-controlled, two-way crossover study of 12 healthy subjects (six men and six women). The study included two 8-day treatment periods with a washout of >or=10 days. In each peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…A two‐way crossover, randomized, study in 12 healthy subjects did not reveal any interaction of ESL (1,200 mg/day for 8 days) with digoxin (on days 1–2, 0.5 mg/day and on days 3–8, 0.25 mg/day) with no effect on digoxin AUC [GMR (90% CI):96% (90–103%)], and a slight decrease of in digoxin – C max [GMR – (90% CI) 85% (68–107%)] in digoxin C max GMR (90% CI) that appears to have no clinical relevance (Vaz‐da‐Silva et al., 2009).…”
Section: Interactions With Other (Non‐aed) Medicationsmentioning
confidence: 99%
“…A two‐way crossover, randomized, study in 12 healthy subjects did not reveal any interaction of ESL (1,200 mg/day for 8 days) with digoxin (on days 1–2, 0.5 mg/day and on days 3–8, 0.25 mg/day) with no effect on digoxin AUC [GMR (90% CI):96% (90–103%)], and a slight decrease of in digoxin – C max [GMR – (90% CI) 85% (68–107%)] in digoxin C max GMR (90% CI) that appears to have no clinical relevance (Vaz‐da‐Silva et al., 2009).…”
Section: Interactions With Other (Non‐aed) Medicationsmentioning
confidence: 99%
“…ESL may not cause QT prolongation, but the evaluation of electrocardiogram recordings during clinical trials showed an increase in PR interval in ESL-treated patients, which was highest in the 1200 mg dose group compared with the placebo group. Finally, ESL was associated with very few psychiatric events, and the incidence of rash was low 12,14,1618,24,2931,35,40,44,45…”
Section: Resultsmentioning
confidence: 97%
“…• Both, coadministration of ESL 1200 mg once daily and digoxin or ESL 1200 mg and metformin were well tolerated and did not influence pharmacokinetics in healthy subjects [44,45];…”
Section: Drug Profilementioning
confidence: 97%